(untitled) (Philological Studies, 2019)
The present paper deals with questions of up to date problems of German linguistics, to be exact the status of the categories of aspectuality, temporality and taxis, their cooperation and peculiarities of actualization of the functionally semantic categories in German. Taking into account that the category of the aspect is not pointed out we can say about the aspectuality as a functionally semantic category. The usage of terminology of the Russian aspectuality in Germanistics determines incorrect interpretation of aspectual meanings in German. The paper focuses on the ideas of A.V. Bondarko concerning the German language which lets imagine the peculiarities of the actualization of temporal aspectual and taxis relations in German from a different point of view.